EFEKTIFITAS STANDARD OPERATING PROCEDURES (SOP) DALAM PELAYANAN PERIZINAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU - Enza Resdiana (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
This research is motivated by the importance of Standard Operating Procedures in services at the Investment and One Stop Service Office of Sumenep Regency. The existence of Standard Operating Procedures in the Office of Investment and One Stop Integrated Services of Sumenep Regency which should improve services to service users has not been achieved by blowing negative issues in the community. This is a phenomenon that needs to be studied and researched more deeply so that a meeting point is found regarding the importance of Standard Operating Procedures in services at the Integrated Licensing Service Agency of Sumenep Regency. This study uses a qualitative research method that explains the importance of Standard Operating Procedures in services at the Investment and One Stop Service Office of Sumenep Regency based on the experience and awareness that occurs in several individuals. Searching and analyzing the importance of Standard Operating Procedures in services at the Investment and One Stop Service Office of Sumenep Regency. Researchers explore information and data in the field by interviewing using a guide to informants, field observations with predetermined observation guidelines, and predetermined field documentation. The results of this study, described through various information and data findings in the field during the research, regarding the importance of Standard Operating Procedures in services at the Investment and One Stop Service Office of Sumenep Regency. Lack of readiness and no evaluation of Standard Operating Procedures makes the service not run optimally. Lack of transparency and clarity of procedures on standard operating procedures to service users causes service users to distrust service users to existing procedures.